2001
DOI: 10.1126/science.291.5502.297
|View full text |Cite
|
Sign up to set email alerts
|

Natal Homing in a Marine Fish Metapopulation

Abstract: Identifying natal origins of marine fishes is challenging because of difficulties in conducting mark-recapture studies in marine systems. We used natural geochemical signatures in otoliths (ear bones) to determine natal sources in weakfish (Cynoscion regalis), an estuarine-spawning marine fish, in eastern North America. Spawning site fidelity ranged from 60 to 81%, comparable to estimates of natal homing in birds and anadromous fishes. These data were in contrast to genetic analyses of population structure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
452
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(465 citation statements)
references
References 20 publications
11
452
0
2
Order By: Relevance
“…Mar Ecol Prog Ser 410: [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195] 2010 the importance of processes that limit dispersal and promote self-replenishment of local populations, such as sedentary adult life history strategies (Robichaud & Rose 2004, Howell et al 2008, spawning site fidelity (Taggart 1997), natal homing (Thorrold et al 2001, Svedäng et al 2007), egg and larval retention (Jones et al 1999, 2005, Bradbury et al 2008) and local adaptation (McIntyre & Hutchings 2003, Conover et al 2006, Hutchings et al 2007). The implications of such fine-scale population structure are important for effective management (Palumbi 2003, Bradbury et al 2008, Reiss et al 2009).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Mar Ecol Prog Ser 410: [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195] 2010 the importance of processes that limit dispersal and promote self-replenishment of local populations, such as sedentary adult life history strategies (Robichaud & Rose 2004, Howell et al 2008, spawning site fidelity (Taggart 1997), natal homing (Thorrold et al 2001, Svedäng et al 2007), egg and larval retention (Jones et al 1999, 2005, Bradbury et al 2008) and local adaptation (McIntyre & Hutchings 2003, Conover et al 2006, Hutchings et al 2007). The implications of such fine-scale population structure are important for effective management (Palumbi 2003, Bradbury et al 2008, Reiss et al 2009).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Quinlan et al (1999) suggested that a cohort could be 'tracked' as it arrived at estuaries, using information from both otolith microchemistry and birth-date distributions. Thorrold et al (2001) compared geochemical signatures in whole otoliths of juvenile weakfish (Cynoscion regalis) with otolith cores of reproductively mature adult weakfish to reveal that many adults were returning to their natal estuary to spawn. Secor and Piccoli (1996) used levels of strontium (which are higher in sea water than fresh water) in otoliths to investigate the distances of up-estuary and down-estuary movement during the growth of striped bass (Morone saxatilis).…”
Section: Juveniles and Adultsmentioning
confidence: 99%
“…Otolith chemical composition has been a particularly valuable tool for marine and fishery ecologists in understanding the spatial ecology of marine fish (Edmonds et al, 1991(Edmonds et al, , 1992Campana and Thorrold, 2001;Thorrold et al, 2001;Gillanders, 2002;Kraus and Secor, 2005). A principal application of otolith microchemistry is to assign widely distributed adults to their natal nursery habitats using otoliths as birth certificates (Secor, 2004) or natural tags (Campana, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Probe-based techniques, including laser ablation ICP-MS, electron probe microanalysis (EPMA) and micro-proton induced X-ray emission (micro-PIXE) are commonly used. Among these techniques, laser ablation ICP-MS is a powerful technique as it combines spot ablation feature of laser with high sensitivity of ICP-MS (Thresher, 1999;Thorrold et al, 2001;Arai and Hirata, 2006;Aria et al, 2007). However, laser ablation ICP-MS suffers from issues of calibration, ablation, fractionation and sample transport.…”
Section: Introductionmentioning
confidence: 99%